Rural Area Development Strategy through Rural Infrastructure Development Program - Suwandi .; Wilmina Pesurnay (Journal of Social and Development Sciences, 2016)
This study was conducted in Biak District of Papua employing the quantitative method. The strategic concept in the development of local institutional capacity was to maximise the role of institutions as social capital not taken over, such as driving as farmers’ cooperatives, cooperatives as agro-tourism objects, and integrating the local institutional system under the auspices of Papua local institutions.